Understanding spatiotemporal changes and influencing factors in the habitat quality of coastal waters: A case study of Jiangsu Province, China (2006–2020) - Zhou Chen; Yanjing Chen; Haifeng Zhang; Hong Zhang; Min Xu (Ecological Indicators)
Habitat quality of coastal waters is under threat from frequent human activities (HA) and pressures from various sources. However, there were few effective and rational explorations of spatiotemporal changes and influencing factors in coastal waters habitat quality. By integrating coastal waters ecology, environment, and HA, an optimized InVEST model was used to assess coastal waters habitat quality which incorporated the benthic biodiversity index. The optimized model was verified through both practical and theoretical assessments. Geographic spatial analysis, Hierarchical Partitioning (HP), and GeoDetector methods were used to explore spatiotemporal changes and influencing factors of habitat quality in the coastal waters of Jiangsu Province over three periods, namely 2006–2010, 2011–2015, and 2016–2020. During the 15-year period, habitat quality declined in 67.63% of Jiangsu Province’s coastal waters. The Plankton Diversity Index (PDI) had the strongest positive impact on coastal waters habitat quality between 2006 and 2010, whereas environmental pollution-related factors, and HA had the least impact. In contrast, the most significant decline in habitat quality between 2011 and 2015 coincided with intense human development and associated environmental challenges. The effects of HA and environmental pollution factors declined, while those of PDI increased between 2016 and 2020. However, potential effects of accumulated environmental pollution were observed, leading to uniform changes in habitat quality. The results indicated that the habitat quality of coastal waters was comprehensively influenced by a combination of factors, including ecological, environmental, and HA. Single factors and multiple factors affected habitat quality in 40.76% and 46.5% of the study area, respectively. This study presents an innovative and scientifically robust method for assessing habitat quality in coastal waters, providing decision-making support for integrated coastal management and sustainable marine development.